Patterns of orthopaedic injury among hospitalised personal mobility device users and bicycle riders: a comparative study - Don Thong Siang Koh; Yew Lok Woo; Ting Hway Wong; Mann Hong Tan (Singapore Medical Journal)
Introduction: Personal mobility devices (PMDs), such as electronic scooters or motorised bicycles, are efficient modes of transportation. Their recent popularity has also resulted in an increase in PMD-related injuries. We aimed to characterise and compare the nature of injuries sustained by PMD users and bicycle riders. Methods: This retrospective study compared injury patterns among PMD and bicycle users. 140 patients were admitted between November 2013 and September 2018. Parameters studied included patients’ demographics (e.g. age, gender and body mass index), type of PMD, nature of injury, surgical intervention required, duration of hospitalisation and time off work. Results: Of 140 patients, 46 (32.9%) patients required treatment at the department of orthopaedic surgery. 19 patients were PMD users while 27 were bicycle riders. 16 (84.2%) patients with PMD-related injuries were men. PMD users were significantly younger (mean age 45 ± 15 years) when compared to bicycle riders (mean age 56 ± 17 years; P <0.05). A quarter (n = 5, 26.3%) of PMD users sustained open fractures and over half (n = 10, 52.6%) required surgical intervention. Among 27 bicycle users, 7.4% (n = 2) of patients sustained open fractures and 70.4% (n = 19) required surgical intervention. Both groups had comparable inpatient stay duration and time off work. Conclusion: PMD-related orthopaedic traumas are high-energy injuries, with higher rates of open fractures, when compared to bicycle injuries. In addition, PMD users are significantly younger and of economically viable age. Prolonged hospitalisation and time off work have socioeconomic implications. Caution should be exercised when using PMDs.